Spremembe pozidanih zemljišč v slovenskih podeželskih naseljih - Bole, David (Georitem, 2007)
Since Slovenia's independence, new economic and social policies have been influencing settlement patterns. Processes which had in fact begun earlier have intensified and deepened during this period, and differences within the country have become greater. The findings from this study could help support a more active land use policy and achieve a better understanding of the structure of built areas within rural settlements.